2021
DOI: 10.1080/09585192.2020.1854816
|View full text |Cite
|
Sign up to set email alerts
|

Team-level high-performance work systems, self-efficacy and creativity: differential moderating roles of person–job fit and goal difficulty

Abstract: Research has examined firm-or unit-level high-performance work systems (HPWS) and impacts on firm, unit, or individual outcomes. Relatively few works have examined how team-level HPWS works together with individual-level factors to shape individual creativity. Grounded in social cognitive theory and the interactionist model of creativity, this study posits and tests the thesis that team-level HPWS and individual-level job characteristics jointly influence individual creativity via individual self-efficacy. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 125 publications
0
24
0
Order By: Relevance
“…When hospitality employees possess the necessary skills to fulfill job demands, they are more inclined to obtain higher D-A fit perceptions. Recently, researchers have begun to combine these two dimensions into the overall P-J fit’s definition (Lam et al , 2018; Ma et al , 2021; Vleugels et al , 2018).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…When hospitality employees possess the necessary skills to fulfill job demands, they are more inclined to obtain higher D-A fit perceptions. Recently, researchers have begun to combine these two dimensions into the overall P-J fit’s definition (Lam et al , 2018; Ma et al , 2021; Vleugels et al , 2018).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Recently, researchers have begun to combine these two dimensions into the overall P-J fit's definition (Lam et al, 2018;Ma et al, 2021;Vleugels et al, 2018). P-E fit theory assumes that environmental factors and individuals' factors could interact to influence individuals' P-J fit perceptions, which could also exert influence on individuals' attitudes and behaviors (Lam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When an employee's original job does not satisfy their needs or prevents them from realizing their value, they may develop the turnover intention to pursue better career development opportunities toward helping them realize this value. According to the "person-job" matching theory (Mobley et al, 1978), when personal characteristics are inconsistent with the professional environment, work efficiency is significantly reduced (Xie et al, 2015;Ma et al, 2021). People's personality characteristics and the professional environment in which they work need to align within a certain matching range.…”
Section: Introductionmentioning
confidence: 99%
“…One of the potential mediators is creativity. This is because P-J fit is positively associated with creativity, while studies have found that creativity has a positive relationship with well-being (Ma et al, 2021;Tan et al, 2021;Tan et al, 2019). Furthermore, a recent study has shown that executive functioning is positively related to work engagement and employee well-being (Nasir et al, 2021).…”
Section: Discussionmentioning
confidence: 99%